1978
DOI: 10.1159/000232111
|View full text |Cite
|
Sign up to set email alerts
|

Mice Bearing the ob/ob Mutation Have Impaired Immunity

Abstract: The obese mutant mouse C57BL/6J ob/ob showed impaired ability to reject skin grafts or react to a contact-sensitising agent in comparison with littermate controls (either +/ob or +/+). Ability of spleen cells from mice bearing the ob/ob mutation to produce a graft-versus-host reaction in C57BL/6J × DBA/2J F1, hybrid mice was not impaired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…recipient [13], Our observation in the obese mouse of a discrepancy between the generation of cyto toxic cells in vivo and in vitro resem bles findings made by Fernandes and col leagues [7] in the phenotypically similar dia betic mouse (C57BL/KsJ db/db). The sim plest explanation for such a discrepancy is that the ob/ob genotype does not produce an irreversible functional change in those cells involved in the generation of a cyto toxic response, but rather produces an envi ronment in which lymphocytes are less able to react to alloantigen.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…recipient [13], Our observation in the obese mouse of a discrepancy between the generation of cyto toxic cells in vivo and in vitro resem bles findings made by Fernandes and col leagues [7] in the phenotypically similar dia betic mouse (C57BL/KsJ db/db). The sim plest explanation for such a discrepancy is that the ob/ob genotype does not produce an irreversible functional change in those cells involved in the generation of a cyto toxic response, but rather produces an envi ronment in which lymphocytes are less able to react to alloantigen.…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that local factors (e.g., low blood supply to the adipose tissue) may be contributory. The impairment in cellular immunity dem onstrated in obese mice both here and in our previous paper [13] suggests a defect in the cellular immune defence mechanism should also be considered. Further, our studies emphasise the importance of mea suring in vivo as well as in vitro parameters of immunological function in studies on the immunological consequences of metabolic disturbances.…”
Section: Clinical Significancesupporting
confidence: 61%
“…These models include animals with a genotype for spontaneously occurring diabetes or animals which have had either streptozotocin-or alloxaninduced diabetes [17,19,21,22]. The C57B-1/65 obl ob mouse has been used in some studies on immune responsiveness in NIDDM [2 11; however, interpretation of immunological studies is confounded by a disproportionately smaller than normal, for the size of animal, spleen and thymus, which contain fewer mononuclear and Thy 1.2-positive lymphocytes, respectively [17,19,211.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether peripheral organs, including the heart, are indeed resistant to the action of leptin, and the potential contribution of impaired cardiac leptin action to abnormal cardiac function in ob/ob mice remains to be elucidated. Leptin signaling has significant effects on immune cells, and defects in innate and adaptive immunity have been described in ob/ob mice (Sheena and Meade, 1978;Meade et al, 1979;La Cava and Matarese, 2004;Matarese et al, 2005;Otero et al, 2006). For example, cardiac injury induced by viral myocarditis is more pronounced in ob/ob mice than in their lean controls, probably owing to a defective T-cell response (Kanda et al, 2004).…”
Section: Disease Models and Mechanisms Dmmmentioning
confidence: 99%